Analisis Penerapan HACCP pada Produksi Keripik Pisang Muli dengan Penggorengan Vakum di UMKM Bandar Lampung - Nurbaiti Nurbaiti; Ulfah Izdihar; Ayu Rahayu Saraswati; Rechal Perdana (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
UMKM XYZ in Bandar Lampung is one of the banana chip producers whose processing uses the vacuum frying method. To ensure the quality of banana chip products is safe for consumers, UMKM must implement an HACCP system. HACCP is used in food products as a safety assurance system. Applying the HACCP system in UMKM can facilitate the business licensing process to penetrate a broader market. This study evaluates critical control points in producing vacuum-fried banana chips using HACCP. Data collection was carried out from February to April 2024, including field observations, interviews with MSME owners, and literature studies, and hazard identification was carried out at each production stage to determine critical control points (CCP) using the CCP decision tree. The study results show that the oil draining and packaging process is a CCP that requires strict control. Potential hazards include physical contaminants such as dust and insects, biological contaminants (molds, bacteria such as salmonella), and chemicals (heavy metals). Control measures include implementing occupational hygiene, using personal protective equipment (PPE), and visual inspection of products and packaging. HACCP can ensure the safety and quality of banana chips produced by analyzing processes that may cause contamination and providing corrective solutions, as well as increasing the competitiveness of UMKMs in the processed food sector.